2023
DOI: 10.1002/jat.4428
|View full text |Cite
|
Sign up to set email alerts
|

The role of receptor‐mediated activities of 4‐ and 5‐ring unsubstituted and methylated polycyclic aromatic hydrocarbons (PAHs) in developmental toxicity

Abstract: The present study evaluated the aryl hydrocarbon receptor (AhR), estrogen receptor‐α (ER‐α), and retinoic acid receptor (RAR) mediated activities of nine 4‐ and 5‐ring unsubstituted and monomethylated polycyclic aromatic hydrocarbons (PAHs) using a series of Chemical‐Activated LUciferase gene eXpression (CALUX) assays. The potential role of these aforementioned receptors in relation to the developmental toxicity of these PAHs was further assessed in the zebrafish embryotoxicity test (ZET). The results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 85 publications
1
0
0
Order By: Relevance
“…As a result, the EC50 values obtained following 24 h exposure to BaP and PAH-containing materials in the AhR CALUX assay are higher than those upon 6 h exposure (EC50 BaP_6h: 6 × 10 –4 μg/ml; EC50 BaP_24h: 1.8 × 10 –2 μg/ml). In line with this observation, it was previously reported that BaP induction is higher after 6 h than after 24 h in the AhR CALUX assay, whereas the reverse was observed for more persistent compounds like TCDD (Hamers et al 2000 ; Machala et al 2001 ; Vrabie et al 2009 ; Fang et al 2023 ). On the contrary, for base oil samples tested (SN100-LBO, SN500-LBO, SN100-BO), the AhR activity was observed only after 6 h but not 24 h exposure, implying a transient or short-lived AhR activation.…”
Section: Discussionsupporting
confidence: 64%
“…As a result, the EC50 values obtained following 24 h exposure to BaP and PAH-containing materials in the AhR CALUX assay are higher than those upon 6 h exposure (EC50 BaP_6h: 6 × 10 –4 μg/ml; EC50 BaP_24h: 1.8 × 10 –2 μg/ml). In line with this observation, it was previously reported that BaP induction is higher after 6 h than after 24 h in the AhR CALUX assay, whereas the reverse was observed for more persistent compounds like TCDD (Hamers et al 2000 ; Machala et al 2001 ; Vrabie et al 2009 ; Fang et al 2023 ). On the contrary, for base oil samples tested (SN100-LBO, SN500-LBO, SN100-BO), the AhR activity was observed only after 6 h but not 24 h exposure, implying a transient or short-lived AhR activation.…”
Section: Discussionsupporting
confidence: 64%